MOTOR DEVELOPMENT THROUGH FUNCTIONAL MUSIC THERAPY IN CHILDREN WITH CEREBRAL PALSY - Kantor, Jiří (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This paper presents an analysis of four case studies in order to elaborate the theory of functional music therapy. In the Czech Republic, the practices of functional music therapy are often used as a type of complementary rehabilitation. Although functional music therapy is based on sound and scientifically substantiated bases, practical applications lack comprehensive and systematic methodology. The aim of this paper is to deepen the knowledge of the links between the application of musical practices and functional development. On the basis of an interpretative approach to case studies (using a content analysis) we identified the objectives in the motor area, types of musical activities, and music therapy practices in persons with cerebral palsy. We also analysed the correlation between therapeutic objectives and musical activities, and set out methodological principles of their application. The outcomes of this study were compared with the results of a previous study by the author focusing on persons with severe multiple disabilities in order to develop a comprehensive theory of functional music therapy. Concerning the results of this comparison, this paper discusses the impact of intellectual disability on the flexibility of application of musical activities during functional training.